The Maternal Serum Preptin Levels in the Pathogenesis and Diagnosis of Gestational Diabetes Mellitus: Preptin and gestational diabetes mellitus - UTKU , Irem KIRAÇ; DEMIR , Esra; OZKAN , Hanişe; SAHTIYANCI , Berrak; EKINCI, Iskender; BUYUKKABA , Mitat; DURMUS, Sinem; AKARSU , Murat; TABAK , Omur; UZUN, Hafize (Journal of Medical Biochemistry, 2022)
Background: Gestational diabetes mellitus (GDM) is a metabolic disorder that occurs during pregnancy that increases both maternal and fetal mortality and morbidity. We investigated whether there is a change in circulating levels of preptin, a new peptide secreted from pancreatic beta cells, due to GDM in pregnant women. The relationship between serum preptin levels with insulin and other metabolic parameters was also evaluated in these subjects. Methods: Eighty-five patients diagnosed as GDM and 89 healthy pregnant women with 75 mg oral glucose tolerance test (OGTT) was assessed in terms of serum preptin levels. Results: The serum preptin levels of the GDM group were significantly higher than those of the control group (p=0.001; p < 0.01). For the cut-off value of preptin measurement of 335.3 ng/L, the sensitivity was 97.65%, specificity was 87.64%, positive predictive value was 88.3% and negative predictive value was 97.5%. The risk of developing the disease is 294.273 times higher in patients with preptin level of 335.3 and above. Conclusions: We think that the reason for the increase in serum preptin levels in GDM is probably the response to glucose. The current results indicate that preptin plays an important role in elucidating the pathology of GDM. In addition, the search for a practical marker for the diagnosis of GDM suggests that the measurement of preptin level is promising.
Keywords: Gestational diabetes mellitus, oral glucose tolerance test, preptin, insulin